Left Dislocation and its translation in some Germanic languages - van der Merwe, Christo H.J. (Stellenbosch Papers in Linguistics Plus, 2016)
In terms of the theoretical framework of an influential recent model of Bible translation, Left Dislocation (=LD) can be regarded as a “communicate clue” that translators must try to interpretively resemble in their target text translation. This exploratory study investigates how twenty translations (fifteen English, three Afrikaans, one German, and one Dutch) have interpretively resembled (or not) nine prototypical constructions, and one less prototypical one, from the book of Genesis. It has been found that, firstly, translations on the formal equivalent pole tend to interpretively resemble LD constructions. If the LD tends to be very prototypical, this tendency is displayed even by some translations towards the functional equivalent pole. Secondly, even in the case of prototypical instances, translations on the functional equivalent pole, however, tend not to interpretively resemble the construction. In these cases, it could be argued that they are not serving the very goal that they as a rule want to accomplish—that is, to provide readers with a translation that is easy to read and process. Thirdly, the structure of English, Afrikaans and Dutch—in contrast to German—often appears to require a construal that does not formally reflect the pronominal resumption of the LD constituent in the matrix clause. Fronting the LD constituent is often used, and sometimes a pause after the fronted (i.e. then dislocated) constituent is signaled by means of a comma or a dash. These findings concur with those of some of the other papers in this volume. Resumption, for example, is not always the primary distinctive feature of a LD construction; a tonal pause between the LD and its matrix clause may also suffice. There are also historical explanations as to why some of the functions of fronting and LD constructions overlap.